SPEED, SIMULTANEITY AND INTERACTION IN NEW MEDIA: A STUDY ON MOBILE APPLICATION NEWS - Ceren Yegen (Selçuk İletişim)
The current and possible effects of the new media are the subject of many studies. Mobile applications are one of the important consequences of the new media, which make traditional communication processes bidirectional and expand communicative local boundaries. Mobile applications, which are used in smartphones and are indispensable for many individual routines, also act as intermediaries in news reporting. So much so that many traditional media organizations such as alternative media formations have created their mobile applications and have started to transmit their news to the users through related applications. It is anticipated that the use of smartphones will spread every day, and when it is thought that the field of journalism is developed on the basis of technology, it can be predicted that the journalism in mobile applications will become widespread. In this study, Hurriyet, Haber Turk and Sabah's mobile applications, which were chosen as representing the Turkish national press, were examined in the context of journalism and structurality. Relevant applications have been compared to the mobile applications of the New York Times, The Guardian and CNN, which have been selected to represent the international press. Thus, it is aimed to analyze mobile application journalism in terms of structurality and ergonomics. The method of study is the hermeneutic approach.